Response of the periapical tissue of dogs' teeth to the action of citric acid and EDTA - Cristina Berthold Sperandio; Luiz Fernando Machado Silveira; Lenita Aver de Araújo; Josué Martos; Ashwin Malshe (University of São Paulo, 2008)
The purpose of this study was to analyze the inflammatory response of dog's periapical tissues to 17% trisodium EDTA salt (pH 8.0) and 1% citric acid (pH 2.0). Saline was used as a control. Six adult dogs were used as the biological model of the study. The experimental units comprised 56 roots of mandibular molars (first and second) and premolars (first, second and third). After coronal opening, pulpectomy and root canal instrumentation were performed using the above-mentioned irrigating solutions. After 24 and 48 hours, the animals were euthanized and the teeth and their supporting tissues were removed and histologically processed. The sections were stained with hematoxylin and eosin and analyzed histopathologically with a light microscope at x100 magnification. The histological analysis focused on the occurrence of acute inflammatory response. The presence of swelling, vasodilatation and inflammatory cells were evaluated and the degree of inflammation was determined for each case. Data were analyzed by Fisher's exact test using the SPSS software with a confidence interval of 95% (p<0.05). 17% EDTA and 1% citric acid caused inflammatory responses in dog's periapical tissues with no significant differences to each other or to saline (control) at either the 24-hour (p=0.482) or 48-hour (p=0.377) periods. It may be concluded that the inflammatory response was of mild intensity for the tested substances.